Association Between Preoperative Lymphocyte-to-Monocyte Ratio and Occurrence of Postoperative Cognitive Dysfunction: A Prospective Cohort Study - Hu X; Zhu S; Yang X; Shan M; Wang J; Da X; Gui Y; Liu Y; Yang R; Xu G (Dove Medical Press, 2024)
Xudong Hu,1,2 Sihui Zhu,1,2 Xiao Yang,1,2 Menglei Shan,1,2 Jiawei Wang,1,2 Xin Da,1,2 Yongkang Gui,1,2 Yang Liu,1,2 Rui Yang,1,2 Guanghong Xu1,2 1Department of Anesthesiology, the First Affiliated Hospital of Anhui Medical University, Hefei, Anhui, People's Republic of China; 2Key Laboratory of Anesthesia and Perioperative Medicine of Anhui Higher Education Institutes, Hefei, Anhui, People's Republic of ChinaCorrespondence: Guanghong Xu, Department of Anesthesiology, the First Affiliated Hospital of Anhui Medical University, 218 Jixi Road, Hefei, Anhui, 230022, People's Republic of China, Tel/Fax +86055162922344, Email xuguanghong2004@163.comPurpose: Postoperative cognitive dysfunction (POCD) is a common postoperative complication. Studies have reported that lymphocyte-to-monocyte ratio (LMR) was a predictor of many diseases associated with inflammation. However, further examination of the relationship between preoperative LMR and POCD is needed. We aimed to investigate the association between POCD and preoperative LMR levels to examine the potential of LMR to predict POCD.Patients and Methods: This was a prospective cohort study that included patients who underwent elective major abdominal surgery at our hospital between January 2019 and January 2022. Multivariate logistic regression analysis was used to analyze the effects of preoperative LMR on POCD development. The optimal threshold of preoperative LMR for predicting POCD was determined by receiver operating characteristic (ROC) approach. A subgroup analysis was performed according to age, sex, type of surgery and hypertension.Results: Of 964 patients, 362 (37.6%) developed POCD. The preoperative LMR level in the Non-POCD group was higher than that in the POCD group. According to the ROC curve, a cutoff value of 3.758 of the preoperative LMR level could be used to predict POCD occurrence and the area under the curve (AUC) was 0.747 (95% CI: 0.715- 0.779, P < 0.001). The results of the subgroup analyses were consistent with the primary ones, and no heterogeneity was observed in the subgroup analyses (P for interaction > 0.05).Conclusion: LMR was significantly associated with the occurrence of POCD after major abdominal surgery. Preoperative low LMR levels can be used to identify patients who may be at high risk of POCD.Keywords: postoperative cognitive dysfunction, lymphocyte-to-monocyte ratio, abdominal surgery, systemic inflammation